(untitled) (Research Announcements "Heritage BG", 2025)
It is noteworthy that most of the cited publications on Jaina statuette-altars, where inscriptions are read, lack their modern language translation. There are no in-depth linguistic analyzes of the monuments, as well as paleographic observations. Obviously, the creation of databases of such epigraphic material is forthcoming, and the sea of such examples is huge. Accepting this text with a specific object of research as an opportunity to introduce the Bulgarian scientific community in general to Jainism and some of its philosophical-aesthetic aspects, we allow ourselves to conclude that the statuette-altar described here is, after all, a souvenir. Objects related to the Jaina cult that can be found by devotees and those interested are still quite limited in India against the backdrop of the vast number of objects related to Buddhism and Hinduism. In this particular case, we have a brass copy of an altar statuette with a central image of Parshva, which repeats a dedicatory inscription of a family living in the late 13th century. It was certainly produced by under-trained master casters who did not know the details of traditional Jaina iconography, and this happened in the middle of the 19th century. The statuette functioned in a family environment, where it was periodically subjected to a ‘purification’ ritual with sandalwood paste and water, which resulted in its smoothing in certain less-than-representative areas of the metal. Here we subjected the artifact to metal testing, which led to the conclusion that not only bronze, but also brass copies of similar images are sold in modern museums and on the antiques market. We also found out that the silver content in the highlight of the central character’s eyes is also important in determining its authenticity.